INVERSION OF THE CONCEPT ABOUT BIOLOGICAL ROLE OF RENIN → ANGIOTENSIN-II → ALDOSTERONE SYSTEM AND FUNCTION OF ARTERIAL BLOOD PRESSURE AS A METABOLISM REGULATOR - V. N. Titov (Евразийский Кардиологический Журнал)
The phylogenetic theory of general pathology postulates an inversion of the concept about the role of arterial blood pressure (AP) in physiology and pathology. Activation of the synthesis of the renin → angiotensin-II (AG-II) system components by nephron and increase in aldosterone secretion are not aimed at elevating AP., but at maintaining the volume of extracellular medium, part of the Third Word Ocean where all cells still live as millions of years ago. Phylogenetically early internal organs cannot regulate the effects of phylogenetically late AP., a physical factor of metabolism. AP is not increased by kidneys, but by the vasomotor center that attempts to reanimate nephronal function, the biological function of endoecology and biological reaction of excretion by increasing AP in proximal and, subsequently, hydrodynamic pressure in the distal region of arterial bed. In addition to the major role in the realization of the biological function of locomotion, AP is a physical factor involved in compensation of impaired functions of homeostasis, trophology, endoecology and adaptation. Levels of metabolism regulation have developed during phylogenesis. Biochemical reactions are specifically regulated at the autocrine level. In paracrine-regulated cell communities of distal arterial bed, metabolism is regulated by millions of local peristaltic pumps by compensating the biological reactions of endothelium-dependent vasodilation, microcirculation, effects of humoral messengers and hormones. In vivo metabolism is regulated nonspecifically from the vasomotor center level by a physical factor (AP) by sympathetic activation of the heart; AP in proximal and distal regions of arterial bed overcomes peripheral resistance and «squeezes through» the arterioles where microcirculation is impaired. AG-II acts as a vasoconstrictor only in the distal arterial bed. In essential (metabolic) arterial hypertension, paracrine cell communities of nephrons and kidneys are involved in realization of pathologic compensation in the second turn and often “suffer being innocent” , similar to other “target” organs”, such as brain, lungs and heart.